India field trip - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Indian agricultural business leaders gathered in September 2015 to discuss ways to transform agricultural production under climate change, a critical challenge for a country that has the second largest worldwide farm output, and is the sixth largest net agricultural exporter worldwide. Their aim is to produce an Action Plan to improve in the way businesses grow food, and develop ambitious targets to improve production resilience and reduce emissions by 2050. To stimulate the discussion, the business leaders, who are members of the World Business Council on Sustainable Development (WBCSD), met with cutting-edge farmers in Haryana, Karnal The business leaders, from major companies such as ITC, Tata, PepsiCo, Olam, UPL, Jain Irrigation and SAB Miller